Ostanki zdravil kot pokazatelj antropogenih vplivov na podzemno vodo Ljubljanskega polja in Ljubljanskega barja - Jamnik, Brigita (Geologija, 2009)
The attention of numerous researches has been recently focused on the determination of pharmaceuticals and other persistent chemicals in the environment. The substances enter groundwater either thorough direct dischargeor indirectly (through surface or waste water). Pharmaceuticals in groundwater can be regarded as artificial tracers that enable the evaluation of general anthropogenic influence on the environment and identification of the most vulnerable areas of aquifers. The article presents the properties of distribution of caffeine, carbamazepine and propyphenazone in the area of Ljubljansko polje and Ljubljansko barje. Ljubljansko polje and Barje are important drinking water resources. These pollutants are indicators of sewage system efficiency, however, in urban areas without sewage they indicate the aquifer's ability of natural attenuation.
Keywords: drug; Ljubljana Marshes; Ljubljansko barje; Ljubljansko polje; onesnaženost; podzemne vode; pollution; vodni viri; vodovarstvena območja; zaščita; zdravila